Parametric optimization of engine performance and emissions for hydroxy blended gaseous fuels - Ijaz Malik, Muhammad Ali; Ikram, Adeel; Sohail, Shayan; Naqvi, Muhammad; Khubaib, Muhammad; Hussain, Fayaz; Zhang, Bo (Elsevier Ltd, 2024)
Gaseous fuels, such as liquefied petroleum gas (LPG) and compressed natural gas (CNG), present a promising alternative to gasoline but with a major drawback due to their lower power output. This study focuses on enhancing power production by combining gaseous fuels with hydroxy gas (HHO), generated via water electrolysis, due to its renewable nature and favorable physiochemical properties. The current study uniquely improves CNG and LPG engine performance by supplementing with HHO gas, compensating for lower efficiency and power than gasoline. Additionally, it innovatively applies response surface methodology (RSM) with a central composite design (CCD) to optimize and analyze fuel blend effects on engine performance. Operating an engine at 1600 to 3400 rpm with a 60 % open throttle, it was observed that, on average, LPG and CNG yielded 23.67 % and 18.91 % lower torque than gasoline. However, adding HHO gas increased torque by 6.57 % for LPG and 6.32 % for CNG. Moreover, LPG-HHO and CNG-HHO blends exhibited 22.66 % and 24.01 % higher brake thermal efficiency (BTE) and 30.44 % and 35.70 % lower brake specific fuel consumption (BSFC) compared to gasoline, respectively. Adding HHO in LPG and CNG reduced CO2 emissions by 7.69 % and 8.2 %, respectively, while increasing NOx emissions by 12.92 % and 12.10 %, respectively. However, this reduction in hazardous pollutant release plays a significant role in ecosystem sustainability. Using RSM, an overall desirability of 0.731 was achieved, pinpointing optimized conditions for a CNG-HHO fuel blend at an engine speed of 2757 rpm. Under such conditions, the observed values were: brake torque of 7.94 Nm, brake power (BP) of 2.14 kW, BSFC of 0.35 kg/kWh, BTE of 23.5 %, CO of 796.24 ppm, CO2 of 6.84 %v, HC of 97.07 ppm, and NOx of 281.6 ppm. Experimental outcomes aligned with the trends predicted by RSM and CCD. Both methodologies highlight the most favorable conditions for the CNG-HHO blend. Applying RSM saves time and minimizes expenses that would otherwise be incurred in extensive experimentation.